Exploring the Rich Diversity of Seagrass Species in Batu Kotak Coastal Ecosystem - Febrisa Indri Utami; Windiarti Pratiwi Putri Nuraini; Novia Intan Cahyani; Lalu Syukran Muhsin; Zahira Rufaida; Ratna Permata Sari (Journal of Biology, Environment, and Edu-Tourism, 2025)
Seagrass ecosystems play a pivotal role in maintaining coastal ecological balance, serving as critical habitats for marine biota, carbon sinks, and natural barriers against erosion. However, anthropogenic pressures increasingly threaten their sustainability. This study aims to assess seagrass diversity in Batu Kotak Beach, Central Lombok, to establish a foundational dataset for conservation efforts. Data were collected across three stations using a quadrat transect method (1×1 m) with three replicates per station. Analyzed parameters included species density, Shannon-Wiener diversity index (H’), evenness (e), and Simpson’s dominance index (C). Results revealed the presence of nine seagrass species, with the highest densities recorded for Syringodium (48 individuals) and Thalassia hemprichii (35 individuals). Diversity indices ranged from low (0.356) to moderate (1.536), with Station III exhibiting the most stable conditions (H’=1.00; e=0.900). Stations I and II displayed pronounced dominance of specific species (Padina tetrastromatica, dominance=0.83), suggesting ecological disturbances. Environmental factors such as water quality, substrate type, and human activities are hypothesized to drive these variations. The study recommends periodic monitoring for Stations I and II and designates Station III as a priority area for conservation.